Rapid, cost-effective and organic solvent-free production of biologically active essential oil from Mediterranean wild Origanum syriacum - Mayadah Shehadeh; Nidal Jaradat; Motasem Al-Masri; Abdel Naser Zaid; Fatima Hussein; Ahmad Khasati; Ghadeer Suaifan; Rula Darwish (Elsevier, 2019)
Background: Origanum syriacum (O. syriacum) is a very popular edible and medicinal plant in the East Mediterranean countries. The aims of the current study were to use microwave-ultrasonic assisted hydrodistillation (MUAHD) method to produce essential oils (EOs) from wild O. syriacum samples collected from four different geographical areas in The West Bank using water as a solvent, determine the phytochemical profile using GC-MS analysis and assess their antioxidant and antibacterial potential. Methods: Essential oils were produced using MUAHD method. Gas chromatography coupled with mass spectrometer detector (GC-MS) was employed for phytochemical analysis. In vitro antibacterial and antioxidant potentials were carried out. Results: Differences in the EOs yield among the four Origanum samples were observed. GC-MS analysis of EOs revealed terpenes as the major constituents; monoterpenes (22-56%) and oxygenated monoterpenes (28-57%). Thymol, α-terpinene and carvacrol represent the bulk of all phytochemicals detected by GC-MS analysis. γ-Terpinene-rich EOs, exhibited the highest antioxidant capacity. Thymol-rich EOs were found to be most effective against Staphylococcus aureus and Methicillin-Resistant Staphylococcus aureus (MRSA) (MIC 390 µg/mL). Alpha-terpinene-rich chemotype EOs exhibited the highest inhibitory effect of Pseudomonas aeruginosa (MIC of 1560 µg/mL). Interestingly, γ-terpinene-rich EO showed promising antibacterial properties against Enterococcus faecium (MIC 97 µg/mL) and a powerful anti-oxidant effect (91.45% ±2.30). Conclusion: The current study supports the use of MUAHD as a time-saving, cost-effective, environment-friendly method for production of high quality O. syriacum EO for potential use as a natural complementary treatment and in the prevention of bacterial infections as well as oxidation by free radicals without compromising the quantity. Keywords: Antibacterial, Antioxidant, Essential oil, GC-MS, Microwave-ultrasonic assisted hydrodistillation, Origanum syriacum